Ecuadorian University Students’ Perception and Attitude Regarding Vaccination against COVID-19 - Lexter Mihalache; Jhonatan Miguel Siguencia Muñoz; Álvaro Paúl Moina Veloz (Medisur)
Foundation: COVID-19 has had a strong impact on global Public Health and has sparked a wide debate about how preventive measures, for example, vaccination, are perceived and approached. Objective: to determine the effectiveness of an educational intervention on perception and attitude of Health Sciences university students regarding vaccination against COVID-19. Method: a quasi-experimental, before-after study without a control group was carried out in a sample of 150 students enrolled in the first year of Health Sciences at the Regional Autonomous University of the Andes. An interview was conducted before and after the intervention and McNemar’s non-parametric test was applied to compare related samples. The intervention consisted of an educational talk and an instructional video. Results: before the intervention it was found that 43.3 % of the students were against vaccination, where the main causes were skepticism due to infodemic and biased information (33.7 %), and fear about safety of the vaccine due to the short duration of clinical trials (22.1 %). After the intervention, it was found that 84 % of the students supported vaccination, results that showed a statistically significant variation. Conclusions: misinformation and fears regarding the effectiveness of vaccines are determining factors for a negative position regarding vaccination against COVID-19. Timely information, personalized to the sociocultural level of the populations, turned out to be an effective strategy in changing opinions regarding vaccination.